Pengaruh Model Problem Based Instruction (PBI) dengan Pendekatan Open Ended Terhadap Pemahaman Konsep dan Kemampuan Penalaran Matematika Siswa - Risnawati Risnawati (Universitas Islam Negeri (UIN) Mataram, 2011)
Given the importance of understanding the concept and the ability in mathematics reasoning for students learn mathematics, the teachers must determine the appropriate learning method that can facilitate students understanding the concepts and the ability reasoning students. One method that can be done is to apply the PBI model with Open Ended Approach. This reseach was conducted to examine whether there are differences in the model PBI with Open Ended approach to the understanding of concepts and the ability in mathematics of reasoning, as well as to obtain information about students' attitudes toward learning mathematics of PBI model with Open Ended approach. This research is a quasi-experimental research with pretest-postes without randomized control groups design. The researsh was conducted in March until April 2012 with 92 students of the fifth Elementary school Muhammadiyah, Kampar District, Kampar regency. The instruments used in this study consisted of testing the understanding of mathematical concepts and reasoning skills, students' attitudes questionnaires, observation sheet, and interview guides. Data analysis was performed by t test. The result of this research showed that there was different of understanding the concept ang the ability in mathematics reasoning between students that were taught PBI model with Open Ended Approach with who were taught using the conventional approach. During learning, most students showed positive attitude towards learning mathematics of PBI model with open ended approach. This was shown by an increase in student activities that the longer the better for learning. Based on the findings of the study, the application of the model PBI with Open Ended approaches can be used as an alternative learning method that can be applied in an effort to improve the understanding of the concepts and mathematical reasoning abilities.